Relationship between cognitive errors and symptoms of attention deficit hyperactivity disorder and substance use characteristics - Örüm, Mehmet Hamdi; Kara, Mahmut Zabit; Kuştepe, Ali; Kalenderoğlu, Aysun (Journal of Dependence, 2019)
Objective: The aim of this study is to investigate the symptoms of attention-deficit/hyperactivity disorder (ADHD) cognitive errors, substance use characteristics and their relation with each other in substance use disorder (SUD). Method: Patients with SUD and control group were administered Adult Attention Deficit Hyperactivity Disorder Self-Report Scale (ASRS), Symptom Check List (SCL-90-R) and obtained sociodemographic data. The cognitive distortions scale (CDS) was used to evaluate cognitive errors. Results: The working status, history of forensic prosecution and psychiatric history were significantly different for the patient group. Significant differences were found between the patient and control groups in terms of the CDS and subscales of cannabis and heroin users. Conclusion: Substance use was associated with bad social-economic-forensic data; the prevalence of ADHD was high in SUD; additional psychiatric symptoms were common in SUD; cognitive errors in SUD were more prominent in cannabis use compared to heroin use; there was a significant correlation between ASRS and CDA-personal achievement and CDS-interpersonal relationship and paranoid symptoms..